Cleavage Requirements of Factor V in Tissue-factor Induced Thrombin Generation - Thorelli, Elisabeth; Kaufman, Randal J.; Dahlbäck, Björn (Thrombosis and Haemostasis, 1998)
Factor V (FV) activation is the result of cleavages at Arg709, Arg1018 and Arg1545 by thrombin or FXa. The relative importance of these cleavages in tissue factor (TF) induced thrombin generation in plasma and in a purified system was elucidated with recombinant FV in which the three sites had been eliminated one by one or in combinations. The mutants were analyzed with a clotting assay using FV-deficient plasma and in a TF induced thrombin generation system using plasma or purified components. Surprisingly, in the standard FV clotting assay, all mutants gave similar clotting activities and the thrombin generation curves obtained with wild-type and thrombin-resistant FV were similar. Differences in clotting activities and thrombin generation patterns between wild-type and thrombin-resistant FV were only observed when lower TF concentrations were used. The thrombin generation curve obtained in plasma containing wt FV was characterized by a short lag phase and a subsequent phase of rapid thrombin generation (propagation phase). The Arg709 to Gln mutation yielded a slightly prolonged lag phase and the rate of thrombin generation during the propagation phase was approximately 5-fold lower than that observed with wt FV. The Arg1018 to Ile mutation only slightly affected the thrombin generation curve, whereas the Arg1545 to Gln mutation yielded a prolonged lag phase and decreased maximum thrombin activity. Thrombin-resistant FV (mutated at all three sites) yielded a prolonged lag phase and poor thrombin generation during the propagation phase. The purified system further demonstrated the importance of the three cleavage sites for rapid and sustained thrombin generation. The results demonstrate that cleavages at positions 709, 1018 and 1545 are not required for assembly of a FXa-FV complex expressing low but significant prothrombinase activity but that all three sites in different ways are important for the creation of a FVa which maximally supports the FXa-mediated activation of prothrombin.